Clostridium perfringens enterotoxin carboxy-terminal fragment is a novel tumor-homing peptide for human ovarian cancer - Azoudi Masoud; Arin-Silasi Dan; Schwartz Peter E; Mor Gil; Montagna Michele K; Fu Han; Holmberg Jennie C; Todeschini Paola; Bellone Marta; Richter Christine E; Bellone Stefania; Casagrande Francesca; et al. (BMC Cancer, 2010)
Abstract Background Development of innovative, effective therapies against recurrent/chemotherapy-resistant ovarian cancer remains a high priority. Using high-throughput technologies to analyze genetic fingerprints of ovarian cancer, we have discovered extremely high expression of the genes encoding the proteins claudin-3 and claudin-4. Methods Because claudin-3 and -4 are the epithelial receptors for Clostridium perfringens enterotoxin (CPE), and are sufficient to mediate CPE binding, in this study we evaluated the in vitro and in vivo bioactivity of the carboxy-terminal fragment of CPE (i.e., CPE290-319 binding peptide) as a carrier for tumor imaging agents and intracellular delivery of therapeutic drugs. Claudin-3 and -4 expression was examined with rt-PCR and flow cytometry in multiple primary ovarian carcinoma cell lines. Cell binding assays were used to assess the accuracy and specificity of the CPE peptide in vitro against primary chemotherapy-resistant ovarian carcinoma cell lines. Confocal microscopy and biodistribution assays were performed to evaluate the localization and uptake of the FITC-conjugated CPE peptide in established tumor tissue. Results Using a FITC-conjugated CPE peptide we show specific in vitro and in vivo binding to multiple primary chemotherapy resistant ovarian cancer cell lines. Bio-distribution studies in SCID mice harboring clinically relevant animal models of chemotherapy resistant ovarian carcinoma showed higher uptake of the peptide in tumor cells than in normal organs. Imunofluorescence was detectable within discrete accumulations (i.e., tumor spheroids) or even single chemotherapy resistant ovarian cancer cells floating in the ascites of xenografted animals while a time-dependent internalization of the FITC-conjugated CPE peptide was consistently noted in chemotherapy-resistant ovarian tumor cells by confocal microscopy. Conclusions Based on the high levels of claudin-3 and -4 expression in chemotherapy-resistant ovarian cancer and other highly aggressive human epithelial tumors including breast, prostate and pancreatic cancers, CPE peptide holds promise as a lead peptide for the development of new diagnostic tracers or alternative anticancer agents.